Reconsidering the relation between fertility and key fertility-related demographic behaviour across space and time - Alexia Prskawetz; Marija Mamolo; Henriette Engelhardt (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2006)
Recent studies on fertility in Europe indicate the changing cross-country correlation between fertility and key fertility-related indicators. Fertility now tends to be lowest in countries that are traditional, catholic and family oriented, while fertility is highest in countries with high divorce rates, high rates of cohabitation and high levels of extra-marital fertility. In this paper we provide support to the argument that the change in the crosscountry correlation between fertility and fertility-related behaviour may indicate a change in social context of this fertility-related behaviour that has helped to uncover cross-country differences in social norms, culture and institutional settings. We apply pooled time series analysis and show that time and country heterogeneity in the effect of key-fertility related behaviour on fertility can explain the change in the cross-country correlation. Our results also indicate that further postponement of key-fertility related behaviour results into less pronounced declines in fertility.
Keywords: 300; Cross-country correlation; low fertility; mean age at first birth; mean age at first marriage; total divorce rate; extra-marital birth; postponement of fertility; pooled time series analysis; Fertilität; Ehe; Sozialer Wandel; Sozialstaat; Schätzung; Europa